2018
DOI: 10.1590/1519-6984.166788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal high fat intake during pregnancy and lactation on total cholesterol and adipose tissue in neonatal rats

Abstract: Aim: Obesity during pregnancy is one of the most established risk factors for negative long-term programming. The aim of the present study was to investigate the effects of maternal consumption of a high-fat diet during pregnancy and lactation on the weight gain, visceral adipose tissue and cholesterolemia in neonatal rats. Methods: Wistar rats were divided into two groups according to the mother's diet during pregnancy and lactation: Control group (CG, n = 12) were the offspring of rats fed a standard diet (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…In addition, we found that pups from mothers fed a HFD had higher serum TC levels at 16 weeks old. Previous studies also found that serum TC levels were persistently higher in offspring from maternal HFD exposure than in those from maternal chow exposure at 3 weeks old (12,40). Moreover, our data showed that maternal HFD exposure led to an increase BAT weight in adult male offspring.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, we found that pups from mothers fed a HFD had higher serum TC levels at 16 weeks old. Previous studies also found that serum TC levels were persistently higher in offspring from maternal HFD exposure than in those from maternal chow exposure at 3 weeks old (12,40). Moreover, our data showed that maternal HFD exposure led to an increase BAT weight in adult male offspring.…”
Section: Discussionsupporting
confidence: 77%
“…BAT "whitening" is related to the progression of obesity. Activation of BAT is a potent target for metabolic diseases, such as diabetes and obesity (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence explains why women with obesity breastfeed for a shorter duration and introduce complementary food earlier than women with normal weight [165]. Moreover, a study conducted by Lima et al in pregnant rats divided into two groups, one control and one fed with a HFD, showed that maternal lipids are reflected in milk composition, and a HFD leads to hypercholesterolemia and visceral fat accumulation in the offspring [166]. Maternal obesity is also associated with the alteration of immunological factor concentrations in human milk, such as C-reactive protein (CRP), leptin, IL-6, insulin, TNF-α, ghrelin, adiponectin, and obestatin.…”
Section: Impact Of Maternal Obesity On Pufa Metabolism During Breastfmentioning
confidence: 99%
“…Animal studies assessing the effect of maternal obesity/ obesogenic diets on offspring adiposity broadly seem to support human association data and show consistent outcomes across species (Table 3). Offspring from obese/highfat diet-fed mothers show increased adiposity [88][89][90] and adipocyte hypertrophy postnatally [89,91]. They also often show increased inflammatory marker expression and a higher infiltration of macrophages and other immune cells in their adipose tissue [89,91,92], which may reflect lipotoxicity and likely contributed to the glucose intolerance seen in such offspring.…”
Section: Maternal Obesity/obesogenic Diets and Offspring Adipositymentioning
confidence: 99%